Faktor- Faktor yang Mempengaruhi Terjadi Kegagalan ASI Eksklusif pada Ibu Menyusui di TPMB Mudrikah Tahun 2024 - Mudrikah, Mudrikah; Jusmawati, Jusmawati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The Central Statistics Agency (BPS) report shows that the percentage of babies under 6 months of age in Indonesia who receive exclusive breast milk (ASI) will reach 73.9% in 2023. The percentage for five consecutive years is the percentage of breastfed babies National exclusives in the country in 2023 will increase by 2.68% compared to the previous year's 72.04%. To determine the factors that influence the failure of exclusive breastfeeding in breastfeeding mothers at TPMB Mudrikah in 2024. The independent variables in this study were age, parity, occupation, pregnancy spacing and the dependent variable was failure to exclusively breastfeed. The sample size in this study used the total side, namely breastfeeding mothers who had babies aged 3-6 months in the work area at TPMB Mudrikah. Data analysis used the chy square test. there is a relationship between parity, occupation, distance between pregnancies and failure to provide exclusive breastfeeding with a P-value <0.05 and there is no relationship between age and failure to provide exclusive breastfeeding with a P-value > 0.05 Conclusions and Suggestions: It is hoped that the results of this research can be developed with different variables so that they can be developed in future research. Keywords: Age, Occupation, Parity, Pregnancy Distance, Exclusive Breastfeeding Failure  ABSTRAK Laporan Badan Pusat Statistik (BPS) menunjukkan presentase bayi berusia di bawah usia 6 bulan di Indonesia yang mendapat air susu ibu (ASI) Ekskusif mencapai 73,9 % pada tahun 2023. Persentase selama lima tahun berturut- turut yaitu presentase bayi ASI Eksklusif nasional di dalam negri pada 2023 naik 2,68% disbanding tahun sebelumnya 72,04%. Untuk Mengetahui Faktor- Faktor Yang Mempengaruhi Terjadi Kegagalan  ASI Eksklusif  Pada Ibu Menyusui di TPMB Mudrikah Tahun 2024. Variabel independen dalam penelitian ini adalah usia, paritas, pekerjaan, jarak kehamilan dan variabel dependennya adalah kegagalan ASI Eksklusif. Besar sampel dalam penelitian ini menggunakan total samping yaitu  ibu  menyusui yang mempunyai bayi usia 3-6 bulan di wilayah kerja di TPMB Mudrikah, Analisa data menggunakan uji chy square. terdapat hubungan paritas, pekerjaan, jarak kehamilan dengan kegagalan pemberian ASI Eksklusif dengan P-value <0,05 dan tidak terdapat hubungan usia dengan kegagalan pemberian ASI Eksklusif dengan P- value > 0,05. Hasil penelitian ini diharapkan dapat di kembangkan dengam variable yang berbeda agar dapat di kembangkan pada penelitan yang akan datang Kata Kunci: Usia, Pekerjaan, Paritas, Jarak Kehamilan, Kegagalan ASI Eksklusif